2020
DOI: 10.1016/j.celrep.2020.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Persisting β Cells Is a Key Feature of Early Type 2 Diabetes Pathogenesis

Abstract: Highlights d Pancreas tissue slices from surgical resections allow study of b cells in T2D d b cell dysfunction develops early and deteriorates further in T2D pathogenesis d Basal and first-phase insulin is altered in impaired glucosetolerant donor tissue d b cell mass in tissue slices appears intact throughout the progression to T2D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 58 publications
(75 reference statements)
6
88
0
1
Order By: Relevance
“…The living pancreas slice technique has allowed us and others to assess numerous parameters of islet cell function from tissues containing the intact endocrine and exocrine compartments (23,(25)(26)(27)(28)(29)(30)(31)(32)(33). We posited that this technological approach would facilitate investigation of structurally altered, infiltrated, or damaged islets during T1D disease pathogenesis, which are thought to be lost during classical islet isolation procedures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The living pancreas slice technique has allowed us and others to assess numerous parameters of islet cell function from tissues containing the intact endocrine and exocrine compartments (23,(25)(26)(27)(28)(29)(30)(31)(32)(33). We posited that this technological approach would facilitate investigation of structurally altered, infiltrated, or damaged islets during T1D disease pathogenesis, which are thought to be lost during classical islet isolation procedures.…”
Section: Resultsmentioning
confidence: 99%
“…The tissue slice technique was developed in the rodent model (23) and optimized for fresh human pancreatic tissue from surgical resections (24,25). In rodents, tissue slices have been shown to be of major value for the study of not only endocrine cell types (e.g., α, β, and δ cells), but also immune, acinar, and vascular cells of the pancreas (24-28, 30, 37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many patient samples (>100) have been assessed for molecular profiling using lasercaptured islets from fixed pancreas samples, it remains to be determined how efficiently this can be adapted to the in vitro assessment of live islets. Importantly, a very recent study [41] has now successfully demonstrated the in vitro islet dysfunction within live pancreas slices from individuals with impaired glucose tolerance or type 2 diabetes.…”
Section: Increasing Scale: Connecting Molecular and Functional Phenotmentioning
confidence: 99%
“…There are 116 million diabetic patients in China, being the largest in the world [1,2]. β-cell deficit is one of the root causes in the development of type 2 diabetes [3,4], and our previous study showed a significant decrease in β-cell mass in Chinese patients with type 2 diabetes [5]. One of the main causes of β-cell deficit in type 2 diabetes is the loss of key transcription factors in mature β cells, which makes β cells back to a "dedifferentiated" state, including NKX6.1 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%